Pengembangan Sistem Informasi Distribusi Guru Berbasis Web Menggunakan Model Rapid Application Development - Niesa, Chaeroen (Jurnal Tika, 2022)
The increasingly widespread use of information technology has an impact on the efficiency of everyday human work. Conventional work models have been abandoned by many people today and switch to work models involving information technology devices, especially computers. One of the cases currently being faced by the Office of the Ministry of Religion of Bireuen Regency is that the distribution process of PNS and Honorary teachers to all madrasas in Bireuen Regency is hampered by the complexity of the problems being faced. The main problem is the difficulty of knowing the teacher needs for each madrasa in the district, because the madrasas are managed not only at the elementary school level, but also at the first and upper levels with a total of about 134 madrasas. This is certainly very difficult if the management of teacher distribution is done manually and conventionally by relying on written records. Therefore, in this study, the development of a madrasah teacher distribution information system in the Ministry of Religion of Bireuen Regency was carried out through the Rapid Application Development (RAD) model approach. The results achieved are that the RAD model is very suitable to be applied to the case of developing teacher distribution information systems because the RAD model involves users directly in the development process, making it easier for developers to map existing business processes. The RAD model also has an impact on the efficiency of application development time being relatively short with a high level of user satisfaction